EWork and eBusiness in architecture, engineering and construction : proceedings of the European Conference on Product and Process Modelling 2012, Reykjavik, Iceland, 25-27 July 2012 /: proceedings of the European Conference on Product and Process Modelling 2012, Reykjavik, Iceland, 25-27 July 2012. (©2012) - Unknown
No abstract available